Using the hydroacoustic and mini trawl data for estimating fish density in the eastern part of Banyuasin coastal waters, South Sumatra of Indonesia - Fauziyah, .; Aprilita, Assyifa M.; Putri, Wike A.E.; Ningsih, Ellis N.; Purwiyanto, Anna I.S.; Agustriani, Fitri (Journal of Fisheries, 2022)
The hydroacoustic and mini trawl sampling was conducted to estimate a distribution pattern of fish density in the eastern part of Banyuasin coastal waters, South Sumatra, Indonesia. These surveys were carried out in September 2017 using a SIMRAD EK15 single‐beam echo sounder with a 200 kHz operating frequency. Catch data obtained from the mini bottom trawl were used to examine a dominant species for refining the TS value concerning the fish density estimation along the hydroacoustic track. The ponyfishes (Eubleekeria jonesi) from the Leiognathidae family were found at each station with the highest relative abundance (50.98%). Hence this species was used to refine target strength values for estimating the acoustic volume density. These volume densities of 206 ESDU ranged from 0 to 9048 fish 1000m–3, with an average of 930 fish 1000m–3. The results also described a distribution pattern of fish densities hence this information could be valuable to the fishery manager for improving sustainable management approaches.